La traduction des éléments culturels dans les versions doublée et sous-titrée en polonais du film américain Madagascar : question de stratégies. - Borowczyk, Paulina (Neophilologica, 2019)
The question of translating cultural aspects is one of the most often raised issues. The aim of this paper is to discuss two main types of translation strategies: target-oriented translation and source-oriented translation. We want to show how they have been defined by different researchers through time. Using contrastive analysis of the original English version of computer-animated comedy film Madagascar (2005; directed by Eric Darnell and Tom McGrath) with dubbed and subtitled Polish versions, the author of this paper examines which strategy is used in case of cultural transfers.